Experiences of Low-Income Indonesian Pregnant Women Regarding the Challenges of Receiving Health Services - Ema Ningrum; Lely Lusmilasari; Emy Huriyati; Mubasysyir Hasanbasri (Shiraz University of Medical Sciences, 2024)
Background: The information needs of low-income pregnant women are multisectoral, encompassing both pregnancy-related and non-pregnancy-related information. Barriers to receiving information for low-income pregnant women are specific and complex. This study aimed to explore the experiences of low-income Indonesian pregnant women regarding the challenges of receiving health information.Methods: A qualitative study was conducted using content analysis according to Graneheim and Lundman's approach between January and June 2022. A total of 17 women were selected for this study using purposive sampling. In-depth interviews were done following semi-structured interview guidelines, concluding when saturation was reached. Nvivo software version March 2020 was used for organizing data and analysis.Results: Three themes emerged concerning receiving health information among low-income women, including encountering barriers to accessing information and care, access to ineffective information sources, and difficulties in applying pregnancy health information.Conclusion: This study shows that barriers to receiving information are specific to low-income pregnant women. Therefore, solution approaches must also be specific. Efforts to improve receiving health information can be achieved through developing educational materials that are easy to access and understand, improving e-health literacy, refining counseling skills among village midwives, holding culturally tailored educational programs, improving mothers' health literacy by family and husbands, integrating counseling with a focus on critical literacy, and formulating policies to alleviate the midwife's workload.